2012
DOI: 10.1158/1078-0432.ccr-12-0552
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Inhibits Hypoxia-Inducible Factor-1α Synthesis: Implications for Antiangiogenic Activity in Hepatocellular Carcinoma

Abstract: Purpose: The overexpression of hypoxia-inducible factor 1a (HIF-1a) is a common finding in hepatocellular carcinoma (HCC), and it leads to angiogenesis and poor prognosis. Sorafenib, a multikinase inhibitor, has shown significant improvement in survival in patients with advanced HCC in clinical trials. However, the mechanisms that account for the antiangiogenic efficiency of sorafenib have not been fully elucidated. The present study aims to explore the effect of sorafenib on HIF-1a expression and activation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 41 publications
(65 reference statements)
6
91
0
Order By: Relevance
“…6D), even though that finding has been reported in other studies. 28,29 Sorafenib did inhibit ERK phosphorylation in PLC/PRF/5 cells in vitro (Fig. 6E), as previously reported.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…6D), even though that finding has been reported in other studies. 28,29 Sorafenib did inhibit ERK phosphorylation in PLC/PRF/5 cells in vitro (Fig. 6E), as previously reported.…”
Section: Discussionsupporting
confidence: 89%
“…We also examined whether sorafenib could inhibit ERK phosphorylation in PLC/ PRF/5 cells in vitro. Consistent with previous reports, 28,29 we found a »50% inhibition of pERK/ERK ratios by band densitometry after a 2 h incubation with 10 mM sorafenib (Fig. 6E).…”
Section: Activity Of Pr-104 and Sorafenib Against Hcc Xenograftssupporting
confidence: 93%
See 1 more Smart Citation
“…We have previously demonstrated that targeting hypoxia-inducible pathways enhanced the antitumor activity of doxorubicin in HCC [4,31] . Although sorafenib downregulates the synthesis of hypoxia-inducible factor (HIF)-1α in HCC cells in vitro and in vivo [32] , the correlation of sorafenib resistance and hypoxic microenvironment is attractive because the antiangiogenic activity of sorafenib is speculated to lead to tumor starvation and subsequent tumor hypoxia [33] . A recent study [34] has shown that sorafenib-resistant HCC tissues had higher expression of HIF-1α than sorafenibsensitive and pre-treated HCC tissues.…”
Section: Hypoxic Microenvironment and Sorafenib Resistancementioning
confidence: 99%
“…Studies also showed that sorafenib had inhibitory effects on HIF-1 activity. 101,102 Temsirolimus (CCI-779, Torisel s ; Pfizer) is an mTOR inhibitor that is approved for RCC. Temsirolimus also inhibited HIF-1a in human lung cancer cell lines under hypoxic conditions.…”
Section: Other Hif-1a Inhibitorsmentioning
confidence: 99%